Environmental arsenic hijacks DDX5-mediated FANCA splicing to impair R-loops resolution and drive ovarian aging - Tuo Zhang; Jin Niu; Lu Yang; Yuanyuan Yu; Meina He; Changfa Wu; Zengmei Cheng; Mei Pan; Zerui Hong; Jian Sun; Yuan Gao; Tengxiang Chen; et al. (Ecotoxicology and Environmental Safety)
Arsenic, a widespread environmental toxicant, is increasingly implicated in female reproductive dysfunction. Long-term exposure to low concentrations of arsenic leads to diminished ovarian reserve. However, the mechanisms by which arsenic exposure accelerates ovarian aging remain unclear. Here, we demonstrate that arsenic exposure induces widespread disruption of pre-mRNA splicing programs in granulosa cells, and these aberrantly spliced genes are predominantly responsible for maintaining genomic stability. Arsenic exposure induces proteasomal degradation of the RNA helicase DDX5 through the UBE3A-mediated ubiquitin-proteasome pathway. Loss of DDX5 impairs the alternative splicing of FANCA, a core gene in the Fanconi anemia pathway, resulting in the production of a truncated isoform. This aberration leads to the excessive accumulation of R-loops and γH2AX-marked DNA damage in ovarian granulosa cells. Consequently, arsenic-exposed mice exhibit hallmark features of premature ovarian aging. Our findings establish the DDX5-FANCA axis as a novel paradigm in which environmental toxins dysregulate RNA splicing, driving reproductive aging through R-loops-mediated genomic instability. These insights highlight splice-switching therapies as a promising strategy to counteract pollutant-induced fertility decline.